ANALYSIS OF WATER QUALITY AND QUALITY STATUS IN ACEH RIVERS BASED ON ENVIRONMENTAL POLLUTION INDEX - Rahmadi, Dicky; Machdar, Izarul; Syaubari, Syaubari (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2022)
The rapid development of industrialization and urbanization in the world impact increased water pollution. Human activities, such as dam constructions, excessive water consumption, severance of river flows, compaction of riverbanks, and excessive use of riverbed vegetation, disrupt river flow and alter the original hydrological cycle. In response to these conditions, this study aims to analyze water quality and river quality status to set up a watershed environmental management strategy in Aceh Province as a case study. River water quality was analyzed descriptively by comparing the results of laboratory tests with parameters, namely TSS, pH, BOD, COD, DO, total phosphate, nitrate, and fecal coli. These parameters were then transformed into the environmental index (Water Quality Index and Pollution Index). It was found that Water Quality Index (WQI) results are shown from 50 to 70. WQI with the Good category is at Kr. Weh which is in the Central Aceh city. The medium-less type is found in 10 watersheds. The water quality with the category of Less is found at 3 points, namely Kr. Aceh, Cr. Doy, and Cr. Daroy. The quality of the river water in the Aceh region, from upstream to downstream, has decreased in quality with a lightly polluted status based on the Minister of Environment and Forestry of the Republic of Indonesia No. 27 of 2021 for class II.